Applied ecology & environmental management - Newman, Edward I. (Wiley-Blackwell, 2000)
A text applying ecological science to the solution of some of the world's more difficult environmental dilemmas. Each chapter considers practical problems, with a clear explanation of the underlying basic science involved with their solution, studied at a variety of scales. Previous edition: c1996. Softcover. DLC: Environmental sciences.